Laser Patterning of Non-Linear Optical Bi2ZnB2O7 Crystal Lines in Glass - Inoue, Taisuke; Gao, Xuyi; Shinozaki, Kenji; Honma, Tsuyoshi; Komatsu, Takayuki (Frontiers in Materials, 2015)
Bi2O3-based glasses are very attractive from the viewpoints of low-melting, high refractive index and crystallization, and the research on their glasses and glass-ceramics is at the frontiers of glass science and technology. Nonlinear optical Bi2ZnB2O7 crystal lines with a high orientation were patterned in 3Sm2O3-30.3Bi2O3-33.3ZnO-33.3B2O3 glass by using a laser-induced crystallization technique. It was confirmed from transmission electron microscope observations that crystals were formed in the inside of the glass, i.e., at the beneath of 4 micro-meter from the surface, although lasers (Yb:YVO4 laser with a wavelength of 1080 nm) were focused at the glass surface. A new potential for optical device applications was added in Bi2O3-based glasses from the present study.